Implementasi Kebijakan Corporate Social Responsibility dalam Meningkatkan Pemberdayaan Masyarakat (Studi pada PT Bank Pembangunan Daerah Lampung Kantor Cabang Metro Tahun 2020) - Syeni Rakhmadani; Joko Mulyono (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
Symptoms of increasing poverty are in line with the multidimensional crisis that occurred in Indonesia. One of the efforts to reduce the poverty rate that can continue to increase is by empowering the community. Community empowerment is one alternative in alleviating poverty. The purpose of this research is that the private sector or company has an obligation to contribute to the environment through the Corporate Social Responsibility Program. This research was conducted using a descriptive qualitative approach. The data used in this study are primary data and secondary data with data analysis techniques proposed by Miles and Hubberman, namely by data reduction, data analysis and drawing conclusions. The results of the study indicate that the implementation of the Corporate Social Responsibility Program in Increasing Community Empowerment at PT Bank Pembangunan Daerah Lampung Metro Branch Office shows that it has had basic steps and clear policy objectives as outlined in the decision of the board of directors No: 153. X/2018 concerning the Management of the Social and Environmental Insurance Fund of PT BPD Lampung, has the main policy source in the form of funds originating from net profit in 2019 with a percentage of 3.1% and 59.5% of funds for community empowerment programs. Communication between organizations has been carried out clearly and consistently. Characteristics The Implementing Body has a clear structure, attitude and tendency for implementers who are very responsive and understand program implementation as well as a very supportive economic and social environment.